Possible Link Between Chronic Periodontal Disease and Central Nervous System Pathologies - Ramírez Chan DDS, MSc, PhD, Karol (Odovtos - International Journal of Dental Sciences, 2015)
Systemic infection and/or inflammation has been related with an increased risk of brain abscesses, cerebrovascular disease, cognitive impairment and other pathological states of the brain. Therefore, it is plausible, that a chronic infection and inflammation disease, such as periodontitis, may affect the central nervous system (CNS). Chronic periodontal disease is a condition that causes breakdown of the supporting tissues of the teeth, alveolar bone and soft tissues. Chronic periodontitis is a multifactorial disease caused by dental plaque composed of pathogenic bacteria that triggers the immune response in susceptible hosts. Oral pathogenic bacteria is a source of chronic infection that can induce local and peripheral production of pro-inflammatory cytokines such as IL-1ß, IL-6 and TNF- , inflammatory mediators, as well as bacterial products such as lipopolysaccaride endotoxin. Viruses, such as herpes and Epstein-Barr, can also be found in periodontal pockets. It is well established that oral pathogenic microorganisms may cause systemic infection by transient or persistent bacteremia, disseminating within the body, and infiltrate distal sites and organs. It has been proposed that in vulnerable populations and under certain circumstances, bacterial and viral infections may enter the brain from the bloodstream. Once in the brain, infectious pathogens and inflammatory products may compromise vascular integrity. Thus, the potential role of the pathogenesis of chronic periodontitis in the development and progression of cerebral infection and inflammation can have a link. There is no direct evidence that determines whether oral diseases have a causal association with CNS pathologies, nonetheless there are several reports that have found oral periodontal pathogens lodged in the brain. Both inflammatory states may just share a casual connection with common risk factors and complex multifactorial etiologies. However, the possibility that pathogenic oral microorganisms disseminate to the bloodstream and reach the brain, initiating or exacerbating existing cerebral lesions, cannot be disregarded. In addition, not only periodontal pathogens may be involved in invading the brain, but also, the pro-inflammatory factors induced systemically by periodontitis, may play a role in CNS pathologies. This oral systemic link will be discussed in this paper.